STUDENTS’ SPEAKING PERFORMANCE IN PRESENTATION CLASS - Retti Nurhayati Agustini (Journal of English Education Program (JEEP), 2018)
This study reports on the students’ speaking performance in presentation class. This study was aimed at finding out: the students’ performance of speaking for academic presentation and the weaknesses and strengths they have in performing speaking for academic presentation. Deborah (2001, p. 1) states that “Presentations are brief discussions of a focused topic delivered to a group of listeners in order to impart knowledge or to stimulate discussion.” The writer took English students at the third grade of English department in Galuh University consisted 20 students. To get the data the writer used two instruments: classroom observation and close ended questionnaire. Then, to interpret the data the writer used qualitative design particularly case study design. The result of this study shows that each student has weaknesses and strengths of each when giving presentations. The prominent strengths when students performing speaking for academic presentation are they did not focus on the notes, they used transitions, their rate speech were not too fast or not too slow and they felt confident to use clear or loud voice. Based on the result of study, it is recommended that students should be more active in practicing their English in groups. It is also suggested that lecturers often implement teaching English speaking through groups.